OCCUPATIONAL CHARACTERISTICS OF 3RD CERVICAL NERVE NEURALGIA: A COMPREHENSIVE REVIEW (European Science Methodical Journal, 2025)
This paper aims to explore the occupational characteristics of third cervical nerve neuralgia (C3 neuralgia), a condition that presents with severe neck pain and radiating discomfort. In particular, it investigates the etiology, diagnosis, and management of this disorder in occupational settings. The focus is on the risk factors present in certain jobs and environments, diagnostic approaches, treatment methods, and preventative strategies.